Anti-cancer effects of aqueous extracts of Dodonaea Viscosa on Burkitt lymphoma - Saferdien, Aaliyah (Department of Pathology, 2026)
Anti-cancer effects of aqueous extracts of Dodonaea Viscosa on Burkitt lymphoma Cancer is a leading public health problem worldwide, and although modern treatments have undeniably improved patient outcomes, many cancers remain refractory or untreatable. New and more effective treatments are needed, and natural phytochemical compounds are a valuable source for the development of such treatments. In South Africa, the high HIV prevalence is a compounding factor in cancer incidence, with some cancers being disproportionately high among HIV-positive individuals. One such cancer is Burkitt lymphoma (BL), a highly aggressive B-cell-derived malignancy, which develops predominantly in HIV-infected individuals. Many cancer patients, especially those from rural communities, use traditional medicine (TM) as an alternative to chemotherapy. While conventional treatments have been thoroughly researched and tested before clinical approval, alternative treatments have not. Therefore, TM may not necessarily be beneficial to patients, could interfere with conventional treatment if used concurrently, and in some instances, be harmful to users. One TM commonly used by communities in the Western Cape regions of South Africa is derived from the plant Dodonaea viscosa. Extracts from this plant have not been widely investigated scientifically, however, preliminary work indicates that it holds potential anti-cancer properties. In the current research, the inhibitory potential of D. viscosa extracts (DVE) on BL was comprehensively assessed, using in vitro assays, as well as using an in vivo mouse model. Using cell viability assays, the IC50 of DVE on two BL cell lines, namely Ramos and BL41, was determined. The Ramos IC50 was 0.06 mg/ml while that of BL41 was 0.18 mg/ml. Notably, the noncancerous lymphoblastoid control cell line (LCL) was significantly less sensitive to DVE compared to both BL cell lines with selectivity indices of 2.8 (using IC50) and 1.7 (using IC30) for Ramos and BL41 respectively. Cell Trace proliferation and colony formation assays showed retardation in the proliferation of extract-treated BL cells (3.2-fold and 10.9-fold reduction in progress to daughter cell generation relative to untreated for Ramos and BL41 respectively). Additionally, DVE induced significant apoptosis, as shown by cellular morphological analyses, Annexin V and caspase 3/7 activity assays, cell cycle profiling and western blotting, showing enhanced expression of effector apoptotic markers (cleaved caspase 3 and cleaved PARP). The PI3K/Akt pathway, which is often altered in BL and known to drive lymphomagenesis, was found to mediate, at least partially, the cytotoxicity of DVE - the PI3K inhibitor p-PTEN was upregulated, leading to upregulation of its target p-PDK1. Additionally, the effector molecule p-AKT (ser 473) and p-GSK3 were altered. Lastly, using a BL xenograft mouse model, DVE was found to be significantly less toxic than the approved drug Doxorubicin, and to slow down tumour growth over time. This study revealed that aqueous extracts from the Dodonaea viscosa plant, used by traditional healers, is a valuable source of lead compounds for the development of novel therapeutics in the treatment of Burkitt lymphoma